Helicobacter Pylori: A Review of Current Treatment Options in Clinical Practice - Logan T. Roberts; Peter P. Issa; Evan S. Sinnathamby; Mallory Granier; Holly Mayeux; Treniece N. Eubanks; Kevin Malone; Shahab Ahmadzadeh; Elyse M. Cornett; Sahar Shekoohi; Alan D. Kaye (Life, 2022)
Background: When prescribing antibiotics, infection eradication rates, local resistance rates, and cost should be among the most essential considerations. Helicobacter pylori is among the most common infections worldwide, and it can lead to burdensome sequela for the patient and the healthcare system, without appropriate treatment. Due to constantly fluctuating resistance rates, regimens must be constantly assessed to ensure effectiveness. Methods: This was a narrative review. The sources for this review are as follows: searching on PubMed, Google Scholar, Medline, and ScienceDirect; using keywords: Helicobacter pylori, Treatment Options, Clinical Practice. Results: Multiple antibiotics are prescribed as part of the regimen to thwart high resistance rates. This can lead to unwanted adverse reactions and adherence issues, due to the amount and timing of medication administration, which also may contribute to resistance. Single-capsule combination capsules have reached the market to ease this concern, but brand-only may be problematic for patient affordability. Due to the previously mentioned factors, effectiveness and affordability must be equally considered. Conclusions: This review will utilize guidelines to discuss current treatment options and give cost considerations to elicit the most effective regimen for the patient.